Assessing Tropical River Water Quality and Pollution Drivers Using CCME-WQI and PCA - Apsari, Selfi'un Linda; Kartikaningsih, Hartati; Pertiwi, Maharani (Civil and Environmental Science Journal (CIVENSE), 2026)
City rivers in rapidly expanding tropical regions face considerable degradation due to domestic wastewater and urban runoff. Our study uses the Canadian Council of Ministers of the Environment Water Quality Index (CCME WQI) and Principal Component Analysis (PCA) to assess water quality in the Gembong River, Pasuruan City. It introduces a new integrative approach by combining the CCME-WQI and PCA to simultaneously assess overall water quality status and identify key pollution-causing parameters along with their seasonal variability, addressing the limitations of previous studies that applied these methods separately without linking pollution sources to temporal dynamics. Sampling was conducted at five stations during the rainy, transitional, and dry seasons. Results showed that all stations fell into the Poor category (WQI 37.71–45.67), with Station 2 exhibiting the lowest quality due to dense settlements and untreated drainage discharge. Seasonal analysis revealed significant variations in fecal coliforms, which peaked during the rainy season due to runoff. PCA identified BOD, COD, and fecal coliform as dominant domestic‑wastewater indicators, while TSS and phosphate reflected land‑use effects. A weak negative correlation between rainfall and BOD–COD suggests continuous wastewater input is the primary driver of pollution. These findings imply that pollution control strategies should prioritize the reduction of BOD, COD, and fecal coliform through improved domestic wastewater treatment systems, particularly in densely populated areas, while TSS and phosphate management should focus on controlling surface runoff and land use practices. These results provide a scientific basis for targeted pollution control and adaptive urban water management strategies to support sustainable river governance.